Elements of Writing Teachers Edition - Kinneavy, James L. (Austin Holt, Rinehart and Winston, 1993)
A teachers guide to using English effectively. Tips on expressive writing, understanding structure, and how to write in certain styles. Information on the origin of English and different parts of speech.
Keywords: Writing